GROWTH, YIELD AND NUTRIENTS CONTENT AND UPTAKE BY GRAIN AND STRAW OF WHEAT AS AFFECTED BY DIFFERENT RESIDUE MANAGEMENT PRACTICES AND NITROGEN LEVELS - K. A. SHAH; B. M. TANDEL; P. NAYAKA (The Bioscan, 2015)
An experiment was conducted during the year 2004-05 and 2005-06, to evaluate the effect of crop residue management practices and nitrogen levels on yield and nutrient content and uptake by wheat. Eighteen treatment combination involving six residue management practices and three levels of nitrogen were tested in factorial randomize block design replicated thrice. Growth and yield attributes of wheat were increased due to different residue management treatments and FYM over control. However, addition of wheat straw @ 5 t ha-1 along with 20 kg N and 20 kg P2O5 ha-1 at 30 days before sowing was produced significantly the highest plant height at harvest, number of effective ear heads, length of era heads, test weight, grain and straw yields of wheat. Nitrogen, phosphorus and potash content and uptake by grain and straw of wheat were also found higher under same treatment. The application of 120 kg N/ha was register significantly the highest all the growth and yield contributing character, including the grain and straw yield of wheat. Similarly, nitrogen, phosphorus and potash content and uptake by grain and straw of wheat were recorded significantly highest under the same treatment.